TESTING ANTECEDENTS OF REVISIT INTENTION - Sitaniapessy, Arthur (Department of Management - Institut Shanti Bhuana, 2024)
This study investigates the impact of customer engagement, memorable tourism experiences, and tourism identification on revisit intention. The population of this research consists of students in the city of Ambon, with a total of 138 respondents. The findings indicate that all three factors—customer engagement, memorable tourism experiences, and tourism identification—positively affect revisit intention. The implications of these findings are highly significant for tourism management and marketing strategies, suggesting that efforts to enhance customer engagement and create memorable experiences can effectively build tourist loyalty and encourage repeat visits. Keywords: customer engagement, memorable tourism experience, tourism identification, revisit intention